Uji penurunan nilai C/N rasio dan kecepatan proses pengomposan tandan kosong kelapa sawit pada beberapa komposisi kotoran sapi - Ilham Manggala Rizkysandy; E. Nanik Kristalisasi; Ryan Firman Syah (Jurnal Pertanian Khairun, 2023)
The research was conducted to know different proportions of cow dung affect the C/N ratio and composting time of empty palm oil bunches is the focus of this study. The study was carried out in Nanggulan Village, Maguwoharjo, Depok, Sleman, Yogyakarta, from March to May 2022. Non-factorial Completely Randomized Design (CRD) with six levels was used to set up this study's factorial experiment including empty oil palm bunches at 100%, 90%, and 0%. Oil palm bunches (empty): 80%, cow manure (10%) The ratio of cow manure to palm fruit bunches is 80:20. 70% empty palm fruit bunches, 30% cow manure 40 percent dried manure from cows, 50 percent dried palm fruit bunches Halves of cow manure. One-way ANOVA was used to examine the study's results. Least Significant Difference (LSD) was used to further test for differences between treatments at the 5% significance level. According to the findings, the C/N ratio was reduced to a best trend of 18.56 in the treatment of 50% empty palm oil bunches + 50% cow dung and to a worst trend of 19.04 in the treatment of 60% empty palm oil bunches + 40% cow dung. Compost is considered mature when it is blackish brown in color, soft in texture, and smells of earth; the pH value at the end of the study was most favorable for the treatment of 70% empty palm oil bunches + 30% cow manure, at 6.6; the temperature in the treatment of 100% empty palm oil bunches was the lowest during the composting process, at 29.00.Keywords: Oil palm empty fruit bunches, cow dung, C/N ratio, activator